AGE-INCLUSIVE PRACTICES AND AGE-FRIENDLY WORKPLACE AS DETERMINANTS OF WORK EFFECTIVENESS IN MULTIGENERATIONAL ORGANIZATIONS - Didit Darmawan; Antonino Pedro Marsal; Jeje Abdul Rojak; Mochamad Irfan; Jony Rodrigues Varela (Jurnal Ilmiah Satyagraha, 2025)
The changing global workforce landscape increasingly requires organizations to implement Age-Inclusive Practices and build Age-Friendly Workplaces to sustainably strengthen work effectiveness in a multigenerational environment. Age-Inclusive Practices, through policies and initiatives that ensure equitable access and development regardless of age, play a crucial role in optimizing the contribution of each employee according to their capacity and uniqueness. This has a direct impact on increasing productivity, work efficiency, and the utilization of diverse generational experiences in the organization. Age-Friendly Workplace focuses on creating a healthy, comfortable and flexible environment, while supporting cross-age collaboration. This kind of work environment increases engagement, accelerates adaptation to change, and strengthens the intergenerational transfer of knowledge that is critical to the continuity of business processes. The synergy of the two concepts has proven to create a more responsive, innovative work system and minimize internal conflicts due to age stereotypes. These practices also reduce turnover and increase loyalty, which directly contributes to stability and work effectiveness at both individual and team levels. The impact can be felt in the improvement of work results, the quality of innovation, and the achievement of organizational goals in an increasingly competitive and dynamic environment. Age-Inclusive Practices and Age-Friendly Workplace build an inclusive corporate culture, and become the main foundation for creating sustainable work effectiveness in the era of multigenerational work.